CRITICAL ANALYSIS ON ASSESSING HEALTH IMPACTS OF CLIMATE CHANGE - 1Bader Ayed Alqarni, 2Nourah Mohammad Abdullah Al shehri, ‏ 3Zainab Rezaq Al-Saadi, ‏4Faten Saud Aljehani, 5Shahad Ali Abdullah Alharbi, 6Saud Deaij Almutairi, ‏7Fadil Msfer yhya Almalki, ‏8Obaid Jamaan Abdullah Alzahrani (Chelonian Research Foundation, 2022)
This article analyzes the different impacts of climate change on wellbeing, counting a few key components. To begin with, significant themes are displayed, followed by a comprehensive literature review to distinguish existing ones. Strategies utilized to degree Health impacts, from epidemiological ponders to demonstrating, are checked on. Visual discoveries are backed by charts, tables, and graphs outlined to demonstrate the conditions observed in air-sensitive wellbeing. These discoveries' suggestions are then talked about, considering their centrality for an public approach, and honed. The record concludes with a few proposals to address the challenges climate change poses to human wellbeing. Bringing together evidence and bits of knowledge from numerous sources, this introductory survey advises the current battle about climate change. It highlights the need for collective activity to decrease dangers and secure public health. Keywords: Climate change, well being impacts, Critical analysis, Literature review, Methodologies, Recommendations